STRUCTURAL STUDY OF THE DRAMA SCRIPT "SENJA DENGAN DUA KELELAWAR" BY KIRDJOMULYO - Deisy Permata Nurfaizar Sari; Lutfi Nurhayati; Trisa Nurfitri; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The literary work of the drama script "Senja dengan Dua Kelelawar" by Kirdjomulyo has urgency in terms of human values, social reality, richness of literary culture, development of science, cultural and social discourse. The aim of this research is to describe the structural elements in the drama script "Senja dengan Dua Kelelawar". Structural analysis is an approach to studying literature from the intrinsic aspects that build the literary work itself. This research method uses a descriptive method with central study data collection techniques. The research results show that the script "Senja dengan Dua Kelelawar" has a theme of romance. This script has eight characters with their respective roles and characters. The flow used is a forward flow. The setting in this text consists of place setting, time setting and social setting. Uses third person omniscient point of view. There are several messages that contain life values ​​that can be learned; a) the importance of honesty to build relationships between people, b) you must learn from mistakes, c) enthusiasm in living a life full of trials. The study of this text can encourage positive changes in various aspects of human life and provide benefits to the general public.